Dark tourism: new road map to resistance, witnessing and healing in contemporary sri lanka - Ahilan, P. (University of Jaffna, 2025)
This research paper examines the complex interplay between Sri Lan- ka's tumultuous past, marked by civil war and the systemic erasure of traumatic histories, and the emerging concept of dark tourism. Dark tourism refers to visits to locations that have historically been connected to the areas of dark heritage such as sites of atrocity, death, disaster, and human depravity as a potential pathway for healing and justice. The physical landscape of Sri Lanka is permeated with remnants of violence, such as mass graves and abandoned sites, which serve as 12 poignant reminders of collective suffering. Utilizing the classical Tamil literary concept of thinai (a poetic device based on ecozones), the paper characterizes the war affected landscape as Kaya perunthinai (wounded earthscape) as where the state machinery's internal colonial tendencies have suppressed narratives of trauma and loss, particularly among minority groups. The discourse on justice remains largely unad- dressed by the state and the NGO initiatives, creating a vacuum that dark tourism could fill. By preserving sites of sorrow and allowing for public engagement with these histories, dark tourism acts as a form of resistance, fostering collective memory and agency among marginal- ized communities. This approach not only aids in confronting physical and psychological traumas but also serves as a cathartic process for survivors, ultimately positioning the acknowledgment of dark pasts as essential for preventing future atrocities and promoting healing.